Endoplasmic reticulum stress in the dorsal root ganglia regulates large‐conductance potassium channels and contributes to pain in a model of multiple sclerosis. Issue 9 (17th July 2020) - Yousuf, Muhammad Saad; Samtleben, Samira; Lamothe, Shawn M.; Friedman, Timothy N.; Catuneanu, Ana; Thorburn, Kevin; Desai, Mansi; Tenorio, Gustavo; Schenk, Geert J.; Ballanyi, Klaus; Kurata, Harley T.; Simmen, Thomas; et al.
Abstract: Neuropathic pain is a common symptom of multiple sclerosis (MS) and current treatment options are ineffective. In this study, we investigated whether endoplasmic reticulum (ER) stress in dorsal root ganglia (DRG) contributes to pain hypersensitivity in the experimental autoimmune encephalomyelitis (EAE) mouse model of MS. Inflammatory cells and increased levels of ER stress markers are evident in post‐mortem DRGs from MS patients. Similarly, we observed ER stress in the DRG of mice with EAE and relieving ER stress with a chemical chaperone, 4‐phenylbutyric acid (4‐PBA), reduced pain hypersensitivity. In vitro, 4‐PBA and the selective PERK inhibitor, AMG44, normalize cytosolic Ca 2+ transients in putative DRG nociceptors. We went on to assess disease‐mediated changes in the functional properties of Ca 2+ ‐sensitive BK‐type K + channels in DRG neurons. We found that the conductance‐voltage (GV) relationship of BK channels was shifted to a more positive voltage, together with a more depolarized resting membrane potential in EAE cells. Our results suggest that ER stress in sensory neurons of MS patients and mice with EAE is a source of pain and that ER stress modulators can effectively counteract this phenotype.